Method for hydrothermal ammonolysis of lignin carbon-based multi-metal catalyst and application

Through the preparation method of hydrothermal ammonia-soluble lignin carbon-based polymetallic catalyst, the existing catalysts have low catalytic activity and many by-products in the ethanol coupling reaction, and efficient ethanol conversion and advanced alcohol yields have been achieved.

CN119771465AActive Publication Date: 2025-04-08GUANGDONG UNIV OF TECH

Patent Information

Application Number
CN202411971013.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing catalysts have low catalytic activity in ethanol coupling reactions and harsh reaction conditions, resulting in low ethanol conversion rate and increased gas by-products.

Method used

Through the preparation method of hydrothermal ammonia-lyzed lignin carbon-based polymetallic catalyst, hydrothermal nitrogen doping and polymetallic synergistic action are adopted to improve the electronic environment and defective structure of the nickel-based catalyst, and enhance the interaction between the metal active components and the lignin-based carbon support.

Benefits of technology

The catalytic activity of the catalyst and the selectivity of the product are improved, the ethanol conversion rate can reach 69.4%, the yield of higher alcohols can reach 50.3%, and the selectivity of gas by-products is only 2.4%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771465A_ABST
    Figure CN119771465A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a hydrothermal ammonolysis lignin carbon-based multi-metal catalyst. The Ni-N-C structure is constructed by a hydrothermal nitrogen doping method to enhance the synergistic effect of the catalytic active component and the lignin carbon-based carrier, and Zn is doped to regulate and control the electronic structure of Ni and effectively inhibit hydrogenolysis and methanation of carbon-carbon bonds in the reaction process, so that the catalytic activity of the catalyst and the selectivity of the product are improved. According to the catalyst obtained by the preparation method, the ethanol conversion rate can reach 69.4%, the yield of higher alcohols can reach 50.3%, the selectivity of gas byproducts is only 2.4%, the catalytic effect is good, and the problems that an existing traditional ethanol Guerbet coupling catalyst is low in ethanol conversion rate, tedious in synthesis process, poor in stability and the like can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysis, and in particular relates to a carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, and a preparation method and application thereof. Background Art

[0002] At present, bioethanol is gradually becoming a sustainable alternative fuel (or fuel additive) to traditional gasoline. However, ethanol as a biofuel has some significant limitations, such as low energy density, hydrophilicity, and corrosion to the engine. Higher alcohols have higher octane number and energy density, hydrophobicity, better mixing stability and compression ignition performance, and have good environmental benefits, so they are considered to be potential biofuels.

[0003] At present, the efficient catalysts used in ethanol coupling experiments mainly include homogeneous iridium, ruthenium complex catalysts, hydroxyapatite catalysts, metal-supported heterogeneous catalysts, etc., which have the advantages of high specific surface area, adjustable acid and base sites, and stable structure; however, these catalysts have disadvantages such as low catalytic activity and harsh reaction conditions, which lead to low ethanol conversion rate and increased gas by-products. Since metal active components such as Ru, Cu, Pt, Co, and Ni have excellent dehydrogenation performance, they are widely used in catalytic related fields such as ethanol coupling. Compared with precious metals, nickel metal has the advantages of high yield and low cost. When nickel metal is loaded on a homogeneous base carrier, it shows excellent ethanol coupling catalytic activity.

[0004] Lignin is abundant in nature and is rich in phenolic hydroxyl, alcoholic hydroxyl, carboxyl and other groups. Its high carbon content makes it an ideal carbon material precursor. Catalysts based on lignin porous carbon materials have higher specific surface area, greater porosity, excellent conductivity and stability, and are also easy to process. Therefore, catalysts prepared by modifying lignin with an appropriate amount of nitrogen doping to increase the alkaline sites on the surface of lignin and anchoring the metal active sites on the nitrogen-doped carbon material have great application potential in ethanol coupling experiments.

[0005] Nickel-based multimetallic catalysts exhibit excellent ethanol coupling catalytic performance. Through nitrogen doping and multimetallic synergy, the electronic environment and defect structure of Ni and carbon carriers can be effectively improved, thereby increasing the stability of the catalyst and effectively inhibiting the formation of byproducts such as methane. Therefore, it has become one of the research hotspots for efficient ethanol coupling catalysts. However, due to the strong metallicity of nickel, Ni has excellent dehydrogenation activity and the ability to break CC bonds / CO bonds, which leads to the formation of gaseous byproducts during the ethanol coupling process and affects the yield of higher alcohols. The low intrinsic activity, less active site exposure and complex preparation process of nickel-based single metal catalysts also make them uncompetitive in the application of ethanol coupling to prepare higher alcohols. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings and defects in the prior art, and thus to provide a hydrothermal ammonolysis of lignin carbon-based multi-metal catalyst, which can effectively enhance the interaction between the metal active components and the lignin-based carbon support through hydrothermal nitrogen doping and multi-metal synergistic action, improve the electronic environment and defect structure of the nickel-based catalyst, and effectively inhibit the hydrogenolysis and methanation of carbon-carbon bonds during the reaction, thereby improving the catalytic activity of the catalyst and the selectivity of the product.

[0007] In order to solve the above technical problems, the present invention is implemented through the following technical solutions.

[0008] The first aspect of the present invention provides a method for preparing a carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, comprising the following steps:

[0009] (1) fully mixing a lignin solution, a nitrogen source, a nickel source, and a metal salt solution, adjusting the pH, and then performing a hydrothermal reaction to synthesize a nitrogen-doped metal-lignin precursor;

[0010] (2) centrifuging and vacuum freeze-drying the doped metal-lignin precursor obtained in step (1) to obtain a metal-lignin synthetic material;

[0011] (3) The metal-lignin synthetic material obtained in step (2) is calcined under a protective gas atmosphere to obtain powder particles, which are then fully ground.

[0012] Preferably, the lignin in step (1) is selected from one or more of longli enzymatic lignin, sulfite lignin, alkali lignin, kraft lignin, and Russian lignin sodium.

[0013] Preferably, the nitrogen source in step (1) is selected from one or more of melamine, cyanuric acid, disodium EDTA, N,N-dimethylformamide, hydroxylamine hydrochloride, diethylenetriamine, ethylenediamine, dicyandiamide, urea and aqueous ammonia.

[0014] Preferably, the nickel source in step (1) is selected from one or more of nickel chloride, nickel sulfate, nickel ammonium nitrate, nickel acetate, nickel oxalate and nickel nitrate; most preferably, the nickel source is selected from nickel nitrate.

[0015] Preferably, the metal salt solution in step (1) is selected from one or more of zinc chloride solution, zinc sulfate solution, copper chloride solution, molybdenum nitrate solution, ferric chloride solution, copper sulfate solution, manganese sulfate solution, ruthenium chloride solution, copper nitrate solution, zinc nitrate solution, zinc acetate solution, zinc oxalate solution, and zinc gluconate solution; more preferably, the metal salt solution is selected from one or more of zinc chloride solution, zinc sulfate solution, zinc nitrate solution, zinc acetate solution, zinc oxalate solution, and zinc gluconate solution; most preferably, the metal salt solution is selected from zinc nitrate solution.

[0016] Preferably, the molar ratio of nickel element to lignin in the nickel source in step (1) is 5-60:1.

[0017] Preferably, in step (1), the molar ratio of the nickel element in the nickel source to the metal element in the metal salt solution is 5-60:1.

[0018] Preferably, in step (1), the amount of lignin used is 2-90wt% of the total mass of the reactants, and the amount of the nitrogen source used is 2-90wt% of the total mass of the reactants.

[0019] Preferably, the mass ratio of lignin to nitrogen source in step (1) is 1:0.1-4; more preferably, the mass ratio of lignin to nitrogen source is 1:0.5-3; most preferably, the mass ratio of lignin to nitrogen source is 1:0.5-1.5.

[0020] Preferably, in step (1), the pH is adjusted to 2-13; more preferably, the pH is adjusted to 7-11; most preferably, the pH is adjusted to 9.

[0021] Preferably, the temperature of the hydrothermal reaction in step (1) is 40-400°C, and the time is 1-64h; more preferably, the temperature of the hydrothermal reaction is 180-230°C, and the time is 6-10h; most preferably, the temperature of the hydrothermal reaction is 195-205°C, and the time is 7-9h.

[0022] Preferably, the rotation speed of the centrifugal treatment in step (2) is 3000-10000 rpm, and the time is 5-30 min.

[0023] Preferably, the vacuum freeze-drying in step (2) is carried out at a temperature of -60 to -40°C and for a time of 12 to 72 hours.

[0024] Preferably, the protective gas in step (3) is selected from one or more of ammonia, nitrogen, argon, air and hydrogen; most preferably, the protective gas is selected from nitrogen.

[0025] Preferably, the calcination temperature in step (3) is 300-1000°C, and the time is 2-12h; more preferably, the calcination temperature is 420-580°C, and the time is 1-3h; most preferably, the calcination temperature is 450-550°C, and the time is 1.5-2.5h.

[0026] A second aspect of the present invention provides a carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin prepared according to the above preparation method.

[0027] The third aspect of the present invention provides the use of the above-mentioned carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin in the preparation of higher alcohols by ethanol coupling.

[0028] When preparing the nitrogen-doped metal-lignin precursor, the present invention adopts a one-pot hydrothermal treatment and a grafting reaction using melamine, ammonia water, etc. as a nitrogen source to uniformly distribute the N element in the carbon material to obtain a modified lignin doped with the N element, and then the modified lignin is coordinated and complexed with the metal active component to obtain the metal-lignin precursor. The catalytic performance of the hydrothermal ammonolysis lignin carbon-based multi-metal catalyst is related to the content of the doping element. With the increase of the alkaline site, the selectivity of n-butanol increases. The present invention then centrifuges the nitrogen-doped metal-lignin precursor and performs vacuum freeze-drying to obtain a metal-lignin synthetic material; then a tubular furnace is used to calcine the prepared metal-lignin synthetic material under an atmosphere of protective gas to obtain a hydrothermal ammonolysis lignin carbon-based multi-metal catalyst (Ni x M y @NC catalyst, x / y is the molar ratio of metal nickel salt to metal salt), and the catalyst performance is optimal when the metal M is selected from Zn. The hydrothermal ammonolysis lignin carbon-based multi-metal catalyst prepared by the present invention is used for ethanol coupling reaction. The ethanol conversion rate of the catalyst can reach 69.4%, the yield of higher alcohols can reach 50.3%, the selectivity of gaseous by-products is only 2.4%, and the catalytic effect is good.

[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0030] (1) When preparing the nitrogen-doped metal-lignin precursor, the present invention greatly enriches the N and O elements of the carbon material by subjecting the lignin to hydrothermal ammonolysis treatment, which helps to improve the precise coordination between lignin and Ni, Zn, Cr, Co, Mn and other ions, thereby making the metal evenly dispersed in the carbon material, in order to improve the applicability of the functionalized lignin carbon-based multi-metal catalyst as a material for converting ethanol into higher alcohols.

[0031] (2) The present invention uses lignin, which has abundant reserves, as a carbon source and melamine and the like as a nitrogen source. The raw material sources are abundant. The catalyst prepared by a one-pot hydrothermal treatment is green and environmentally friendly. The preparation process is simple and energy-saving, creating conditions for the industrial application of a hydrothermal ammonolysis lignin carbon-based multi-metal catalyst. In addition, by doping Zn and the like to regulate the electronic structure of Ni and increase the defect structure of the carbon material, the hydrogenolysis and methanation of the carbon-carbon bond during the reaction are effectively inhibited, thereby improving the catalytic activity of the catalyst and the selectivity of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a scanning electron microscope image of the carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin prepared in Example 2 of the present invention.

[0033] Figure 2 This is a transmission electron micrograph of the carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin prepared in Example 2 of the present invention.

[0034] Figure 3 This is a high-resolution transmission electron micrograph of the carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin prepared in Example 2 of the present invention.

[0035] Figure 4 This is the EDS elemental map of nickel, nitrogen and carbon elements of the carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] Unless otherwise defined, all technical terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or can be prepared by existing methods.

[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The lignin used in the embodiments of the present invention and the comparative examples are all alkali lignin (AL) as an example. It should be understood that lignin is only used as a raw material to provide a carbon source, and its specific type has no significant effect on the properties of the finished catalyst. When other lignin types such as Longli enzymatic lignin, sulfite lignin, kraft lignin, Russian wood sodium, etc. are used to prepare the catalyst, the obtained catalyst performance is not significantly different from that of alkali lignin, so they are not listed one by one here.

[0039] Example 1

[0040] A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0041] (1) Lignin is dissolved in ammonia water to prepare a lignin solution, and then the lignin solution, nickel acetate solution, zinc nitrate solution and melamine are placed in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, the pH is adjusted to 9, and the mixture is hydrothermally reacted at 200°C for 8 hours to synthesize a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, ammonia water, nickel acetate, zinc nitrate and melamine are 2.71%, 1.36%, 2.14%, 0.14% and 2.71%, respectively, and the balance is water.

[0042] (2) centrifuging the doped metal-lignin precursor obtained in step (1) at 10,000 rpm for 10 min, taking the solid precipitate and freeze-drying it at -50°C in vacuum for 72 h to obtain a metal-lignin synthetic material;

[0043] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 500° C. in a nitrogen atmosphere for 2 h, and after natural cooling, powder particles are obtained, which are then fully ground.

[0044] In the ethanol coupling experiment, using the hydrothermal ammonolysis of lignin carbon-based multi-metal catalyst prepared in this example, the ethanol conversion rate can reach 67.3%, the yield of higher alcohols can reach 47.2%, and the gas by-product selectivity is 3.7%.

[0045] Example 2

[0046] A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0047] (1) Lignin is dissolved in ammonia water to prepare a lignin solution, and then the lignin solution, nickel nitrate solution, zinc nitrate solution and melamine are placed in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, the pH is adjusted to 9, and the mixture is hydrothermally reacted at 200°C for 8 hours to synthesize a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, ammonia water, nickel nitrate, zinc nitrate and melamine are 2.71%, 1.36%, 2.14%, 0.14% and 2.71%, respectively, and the balance is water.

[0048] (2) centrifuging the doped metal-lignin precursor obtained in step (1) at 10,000 rpm for 10 min, taking the solid precipitate and freeze-drying it at -50°C in vacuum for 72 h to obtain a metal-lignin synthetic material;

[0049] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 500° C. in a nitrogen atmosphere for 2 h, and after natural cooling, powder particles are obtained, which are then fully ground.

[0050] In the ethanol coupling experiment, using the hydrothermal ammonolysis of lignin carbon-based multi-metal catalyst prepared in this example, the ethanol conversion rate can reach 69.4%, the yield of higher alcohols can reach 50.3%, and the gas by-product selectivity is 2.4%.

[0051] The scanning electron microscopy and transmission electron microscopy images of the carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin prepared in this example are shown in Figure 1 , Figure 2 As shown in the figure, it can be seen that the carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin prepared in this embodiment has a flaky thin layer structure and a rich pore structure.

[0052] The high-resolution transmission electron microscopy image and pore size distribution diagram of the carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin prepared in this example are shown in Figure 3 As shown in the figure, it can be seen that the Ni of the hydrothermal ammonolysis of lignin carbon-based multi-metal catalyst prepared in this embodiment is wrapped in the amorphous carbon material, exposing lattice fringes with a crystal plane spacing of 0.201 nm, corresponding to the Ni (111) crystal plane in the XRD spectrum. Figure 4 It can be clearly observed that nickel, nitrogen and carbon elements are evenly distributed on the sample.

[0053] Example 3

[0054] A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0055] (1) Lignin is dissolved in ammonia water to prepare a lignin solution, and then the lignin solution, nickel nitrate solution, zinc acetate solution and melamine are placed in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, the pH is adjusted to 9, and the mixture is hydrothermally reacted at 200°C for 8 hours to synthesize a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, ammonia water, nickel nitrate, zinc acetate and melamine are 2.71%, 1.36%, 2.14%, 0.14% and 2.71%, respectively, and the balance is water.

[0056] (2) centrifuging the doped metal-lignin precursor obtained in step (1) at 10,000 rpm for 10 min, taking the solid precipitate and freeze-drying it at -50°C in vacuum for 72 h to obtain a metal-lignin synthetic material;

[0057] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 500° C. in a nitrogen atmosphere for 2 h, and after natural cooling, powder particles are obtained, which are then fully ground.

[0058] In the ethanol coupling experiment, using the hydrothermal ammonolysis lignin carbon-based multi-metal catalyst prepared in this example, the ethanol conversion rate can reach 68.2%, the yield of higher alcohols can reach 48.1%, and the gas by-product selectivity is 3.6%.

[0059] Comparative Example 1

[0060] A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0061] (1) Lignin is dissolved in ammonia water to prepare a lignin solution, and then the lignin solution, nickel nitrate solution, zinc nitrate solution and melamine are placed in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, the pH is adjusted to 9, and the mixture is hydrothermally reacted at 200°C for 4 hours to synthesize a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, ammonia water, nickel nitrate, zinc nitrate and melamine are 2.71%, 1.36%, 2.14%, 0.14% and 2.71%, respectively, and the balance is water.

[0062] (2) centrifuging the doped metal-lignin precursor obtained in step (1) at 10,000 rpm for 10 min, taking the solid precipitate and freeze-drying it at -50°C in vacuum for 72 h to obtain a metal-lignin synthetic material;

[0063] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 500° C. in a nitrogen atmosphere for 2 h, and after natural cooling, powder particles are obtained, which are then fully ground.

[0064] In the ethanol coupling experiment, using the hydrothermal ammonolysis of lignin carbon-based multi-metal catalyst prepared in this example, the ethanol conversion rate can reach 45.2%, the yield of higher alcohols can reach 32.2%, and the gas by-product selectivity is 7.2%.

[0065] Comparative Example 2

[0066] A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0067] (1) Lignin is dissolved in ammonia water to prepare a lignin solution, and then the lignin solution, nickel nitrate solution, zinc nitrate solution and melamine are placed in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, the pH is adjusted to 9, and the hydrothermal reaction is carried out at 200°C for 6 hours to synthesize a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, ammonia water, nickel nitrate, zinc nitrate and melamine are 2.71%, 1.36%, 2.14%, 0.14% and 2.71%, respectively, and the balance is water.

[0068] (2) centrifuging the doped metal-lignin precursor obtained in step (1) at 10,000 rpm for 10 min, taking the solid precipitate and freeze-drying it at -50°C in vacuum for 72 h to obtain a metal-lignin synthetic material;

[0069] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 500° C. in a nitrogen atmosphere for 2 h, and after natural cooling, powder particles are obtained, which are then fully ground.

[0070] In the ethanol coupling experiment, using the hydrothermal ammonolysis lignin carbon-based multi-metal catalyst prepared in this example, the ethanol conversion rate can reach 51.3%, the yield of higher alcohols can reach 38.2%, and the gas by-product selectivity is 5.1%.

[0071] Comparative Example 3

[0072] A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0073] (1) Lignin is dissolved in ammonia water to prepare a lignin solution, and then the lignin solution, nickel nitrate solution, zinc nitrate solution and melamine are placed in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, the pH is adjusted to 9, and the hydrothermal reaction is carried out at 200°C for 10 hours to synthesize a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, ammonia water, nickel nitrate, zinc nitrate and melamine are 2.71%, 1.36%, 2.14%, 0.14% and 2.71%, respectively, and the balance is water.

[0074] (2) centrifuging the doped metal-lignin precursor obtained in step (1) at 10,000 rpm for 10 min, taking the solid precipitate and freeze-drying it at -50°C in vacuum for 72 h to obtain a metal-lignin synthetic material;

[0075] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 500° C. in a nitrogen atmosphere for 2 h, and after natural cooling, powder particles are obtained, which are then fully ground.

[0076] In the ethanol coupling experiment, using the hydrothermal ammonolysis lignin carbon-based multi-metal catalyst prepared in this example, the ethanol conversion rate can reach 49.4%, the yield of higher alcohols can reach 37.4%, and the gas by-product selectivity is 7.6%.

[0077] Comparative Example 4

[0078] A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0079] (1) Lignin is dissolved in ammonia water to prepare a lignin solution, and then the lignin solution, nickel nitrate solution, zinc nitrate solution and melamine are placed in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, the pH is adjusted to 9, and the hydrothermal reaction is carried out at 180°C for 8 hours to synthesize a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, ammonia water, nickel nitrate, zinc nitrate and melamine are 2.71%, 1.36%, 2.14%, 0.14% and 2.71%, respectively, and the balance is water.

[0080] (2) centrifuging the doped metal-lignin precursor obtained in step (1) at 10,000 rpm for 10 min, taking the solid precipitate and freeze-drying it at -50°C in vacuum for 72 h to obtain a metal-lignin synthetic material;

[0081] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 500° C. in a nitrogen atmosphere for 2 h, and after natural cooling, powder particles are obtained, which are then fully ground.

[0082] In the ethanol coupling experiment, using the hydrothermal ammonolysis of lignin carbon-based multi-metal catalyst prepared in this example, the ethanol conversion rate can reach 62.1%, the yield of higher alcohols can reach 45.6%, and the gas by-product selectivity is 8.2%.

[0083] Comparative Example 5

[0084] A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0085] (1) Lignin is dissolved in ammonia water to prepare a lignin solution, and then the lignin solution, nickel nitrate solution, zinc nitrate solution and melamine are placed in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, the pH is adjusted to 9, and the hydrothermal reaction is carried out at 190° C. for 8 hours to synthesize a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, ammonia water, nickel nitrate, zinc nitrate and melamine are 2.71%, 1.36%, 2.14%, 0.14% and 2.71%, respectively, and the balance is water.

[0086] (2) centrifuging the doped metal-lignin precursor obtained in step (1) at 10,000 rpm for 10 min, taking the solid precipitate and freeze-drying it at -50°C in vacuum for 72 h to obtain a metal-lignin synthetic material;

[0087] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 500° C. in a nitrogen atmosphere for 2 h, and after natural cooling, powder particles are obtained, which are then fully ground.

[0088] In the ethanol coupling experiment, using the hydrothermal ammonolysis of lignin carbon-based multi-metal catalyst prepared in this example, the ethanol conversion rate can reach 64.3%, the yield of higher alcohols can reach 47.3%, and the gas by-product selectivity is 7.5%.

[0089] Comparative Example 6

[0090] A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0091] (1) Lignin is dissolved in ammonia water to prepare a lignin solution, and then the lignin solution, nickel nitrate solution, zinc nitrate solution and melamine are placed in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, the pH is adjusted to 9, and the hydrothermal reaction is carried out at 210°C for 8 hours to synthesize a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, ammonia water, nickel nitrate, zinc nitrate and melamine are 2.71%, 1.36%, 2.14%, 0.14% and 2.71%, respectively, and the balance is water.

[0092] (2) centrifuging the doped metal-lignin precursor obtained in step (1) at 10,000 rpm for 10 min, taking the solid precipitate and freeze-drying it at -50°C in vacuum for 72 h to obtain a metal-lignin synthetic material;

[0093] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 500° C. in a nitrogen atmosphere for 2 h, and after natural cooling, powder particles are obtained, which are then fully ground.

[0094] In the ethanol coupling experiment, using the hydrothermal ammonolysis of lignin carbon-based multi-metal catalyst prepared in this example, the ethanol conversion rate can reach 64.5%, the yield of higher alcohols can reach 46.5%, and the gas by-product selectivity is 9.1%.

[0095] Comparative Example 7

[0096] A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0097] (1) Lignin is dissolved in ammonia water to prepare a lignin solution, and then the lignin solution, nickel nitrate solution, zinc nitrate solution and melamine are placed in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, the pH is adjusted to 9, and the mixture is hydrothermally reacted at 200°C for 8 hours to synthesize a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, ammonia water, nickel nitrate, zinc nitrate and melamine are 2.71%, 1.36%, 2.14%, 0.14% and 2.71%, respectively, and the balance is water.

[0098] (2) centrifuging the doped metal-lignin precursor obtained in step (1) at 10,000 rpm for 10 min, taking the solid precipitate and freeze-drying it at -50°C in vacuum for 72 h to obtain a metal-lignin synthetic material;

[0099] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 400° C. in a nitrogen atmosphere for 2 h, and after natural cooling, powder particles are obtained, which are then fully ground.

[0100] In the ethanol coupling experiment, using the hydrothermal ammonolysis of lignin carbon-based multi-metal catalyst prepared in this example, the ethanol conversion rate can reach 43.2%, the yield of higher alcohols can reach 35.5%, and the gas by-product selectivity is 9.8%.

[0101] Comparative Example 8

[0102] A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0103] (1) Lignin is dissolved in ammonia water to prepare a lignin solution, and then the lignin solution, nickel nitrate solution, zinc nitrate solution and melamine are placed in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, the pH is adjusted to 9, and the mixture is hydrothermally reacted at 200°C for 8 hours to synthesize a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, ammonia water, nickel nitrate, zinc nitrate and melamine are 2.71%, 1.36%, 2.14%, 0.14% and 2.71%, respectively, and the balance is water.

[0104] (2) centrifuging the doped metal-lignin precursor obtained in step (1) at 10,000 rpm for 10 min, taking the solid precipitate and freeze-drying it at -50°C in vacuum for 72 h to obtain a metal-lignin synthetic material;

[0105] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 600° C. in a nitrogen atmosphere for 2 h, and then naturally cooled to obtain powder particles, which are then fully ground.

[0106] In the ethanol coupling experiment, using the hydrothermal ammonolysis lignin carbon-based multi-metal catalyst prepared in this example, the ethanol conversion rate can reach 42.5%, the yield of higher alcohols can reach 32.3%, and the gas by-product selectivity is 8.3%.

[0107] Comparative Example 9

[0108] A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0109] (1) Lignin is dissolved in ammonia water to prepare a lignin solution, and then the lignin solution, nickel nitrate solution, zinc nitrate solution and melamine are placed in a beaker in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, and then heated to 100° C. and stirred until the water is completely evaporated to obtain a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, ammonia water, nickel nitrate, zinc nitrate and melamine are 2.7%, 1.4%, 2.1%, 0.1% and 2.7%, respectively, and the balance is water.

[0110] (2) placing the doped metal-lignin precursor obtained in step (1) in an oven at 90° C. to completely dry it, and grinding it into powder to obtain a metal-lignin synthetic material;

[0111] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 500° C. in a nitrogen atmosphere for 2 h, and after natural cooling, powder particles are obtained, which are then fully ground.

[0112] In the ethanol coupling experiment, using the hydrothermal ammonolysis of lignin carbon-based multi-metal catalyst prepared in this example, the ethanol conversion rate can reach 56.4%, the yield of higher alcohols can reach 34.2%, and the gas by-product selectivity is 8.9%.

[0113] Comparative Example 10

[0114] A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0115] (1) Lignin is dissolved in ammonia water to prepare a lignin solution, and then the lignin solution, nickel nitrate solution and zinc nitrate solution are placed in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, the pH is adjusted to 9, and the hydrothermal reaction is carried out at 200° C. for 8 hours to synthesize a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, ammonia water, nickel nitrate and zinc nitrate are 2.79%, 1.4%, 2.2% and 0.14%, respectively, and the balance is water.

[0116] (2) centrifuging the doped metal-lignin precursor obtained in step (1) at 10,000 rpm for 10 min, taking the solid precipitate and freeze-drying it at -50°C in vacuum for 72 h to obtain a metal-lignin synthetic material;

[0117] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 500° C. in a nitrogen atmosphere for 2 h, and after natural cooling, powder particles are obtained, which are then fully ground.

[0118] In the ethanol coupling experiment, using the hydrothermal ammonolysis lignin carbon-based multi-metal catalyst prepared in this comparative example, the ethanol conversion rate can reach 64.6%, the yield of higher alcohols can reach 45.1%, and the gas by-product selectivity is 6.9%.

[0119] Comparative Example 11

[0120] A carbon-based catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0121] (1) Lignin is dissolved in ammonia water to prepare a lignin solution, and then the lignin solution, nickel nitrate solution and melamine are placed in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, the pH is adjusted to 9, and the hydrothermal reaction is carried out at 200°C for 8 hours to synthesize a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, ammonia water, nickel nitrate and melamine are 2.72%, 1.36%, 2.15% and 2.72%, respectively, and the balance is water.

[0122] (2) centrifuging the doped metal-lignin precursor obtained in step (1) at 10,000 rpm for 10 min, taking the solid precipitate and freeze-drying it at -50°C in vacuum for 72 h to obtain a metal-lignin synthetic material;

[0123] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 500° C. in a nitrogen atmosphere for 2 h, and after natural cooling, powder particles are obtained, which are then fully ground.

[0124] In the ethanol coupling experiment, using the hydrothermal ammonolysis lignin carbon-based catalyst prepared in this comparative example, the ethanol conversion rate can reach 66.6%, the yield of higher alcohols can reach 38.7%, and the gas by-product selectivity is 9.1%.

[0125] Comparative Example 12

[0126] A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, the preparation method of which comprises the following steps:

[0127] (1) Lignin is dissolved in a sodium hydroxide solution to prepare a lignin solution, and then the lignin solution, nickel nitrate solution, zinc nitrate solution and melamine are placed in a hydrothermal kettle, stirred at room temperature for 30 minutes to fully mix, the pH is adjusted to 9, and the mixture is hydrothermally reacted at 200°C for 8 hours to synthesize a black nitrogen-doped metal-lignin precursor; wherein the mass fractions of lignin, sodium hydroxide, nickel nitrate, zinc nitrate and melamine are 2.71%, 0.8%, 2.14%, 0.14% and 2.17%, respectively, and the balance is water.

[0128] (2) centrifuging the doped metal-lignin precursor obtained in step (1) at 10,000 rpm for 10 min, taking the solid precipitate and freeze-drying it at -50°C in vacuum for 72 h to obtain a metal-lignin synthetic material;

[0129] (3) The metal-lignin synthetic material obtained in step (2) is calcined at 500° C. in a nitrogen atmosphere for 2 h, and after natural cooling, powder particles are obtained, which are then fully ground.

[0130] In the ethanol coupling experiment, using the hydrothermal ammonolysis lignin carbon-based multi-metal catalyst prepared in this example, the ethanol conversion rate can reach 41.6%, the yield of higher alcohols can reach 26.3%, and the gas by-product selectivity is 8.1%.

[0131] Verification Example 1

[0132] Ni prepared with different raw material ratios x Zn y@NC catalyst can catalyze the conversion of ethanol into higher alcohols by coupling. The aqueous and oil phase products produced by the ethanol coupling experiment were analyzed by GC, and the gas products produced by the ethanol coupling experiment were analyzed by TCD and FID, and the data in Table 1 were obtained. From the results in Table 1, it can be seen that when melamine and urea are used as nitrogen sources, nickel nitrate and zinc nitrate are used as metal salts, the mass fractions of lignin, ammonia water, melamine, nickel nitrate and zinc nitrate are 2.71%, 1.36%, 2.71%, 2.14% and 0.14% respectively, and the hydrothermal temperature is 200℃, the hydrothermal time is 8h, and the calcination temperature is 500℃, the catalyst has the best effect in catalyzing the synthesis of higher alcohols, the ethanol conversion rate can reach 69.4%, the yield of higher alcohols can reach 50.3%, and the selectivity of gas by-products is 2.4%.

[0133] Through a large number of studies, the present invention finds that selecting a suitable nitrogen-containing reagent to provide N doping can effectively disperse Ni grains and improve catalytic activity; at the same time, N doping is conducive to the generation of defect structures, and the construction of Ni-NC structure helps to improve the synergistic effect of metal active components and lignin-based carbon carriers, and Zn doping can also improve the Ni electronic structure, improve the stability of the metal on the carbon-based support through the bonding between the N position and Ni and Zn metal atoms, and increase the dispersion of metal active components to provide more active sites; N doping can accurately regulate the electronic structure of Ni, promote the charge redistribution between the carrier and the NiZn catalyst, and make the metal cluster present a less positive charge state, thereby weakening the excessive dehydrogenation of the metal active site, enhancing the desorption behavior of the intermediate (such as CH3CHO*), and finally promoting the CC coupling reaction and inhibiting further dehydrogenation and CC bond cleavage; when applied to the ethanol coupling reaction, it can effectively inhibit CC bond cleavage and improve the selectivity of the target product. For nitrogen sources, melamine and ammonia water are the best choices. While ammonia water serves as a partial nitrogen source, it also makes the lignin evenly dispersed in the solution, which helps to better carry out the grafting reaction and metal loading. With the addition of melamine, melamine decomposes during the pyrolysis process to produce a large amount of volatile gases, which destroy the dense carbon skeleton, form a layered porous nanolayer structure and increase the specific surface area of ​​the catalyst.

[0134] At the same time, the amount of melamine has a significant effect on the performance of the catalyst. However, when the mass ratio of melamine to lignin is too high, the specific surface area of ​​the catalyst will be significantly reduced, which may be due to the fact that excessive melamine inhibits the growth of carbon nanostructures, resulting in a lower specific surface area. The high specific surface area provides enhanced metal anchoring sites, increases the dispersion of metals, and is conducive to the exposure of active sites, which is conducive to the adsorption process, thereby providing the catalyst with the possibility of good catalytic activity. Mesopores of about 2nm can provide a suitable pathway for the penetration and transportation of reactants, making it easier for reactants to diffuse to active sites, which is conducive to the mass transfer process, promoting rapid diffusion on the catalyst, reducing the deposition of reactants and products on the catalyst, and reducing the occurrence of side reactions. Mesoporous materials can promote the fixed distribution of metal particles. In addition, metal particles wrapped in the carbon skeleton can effectively avoid particle aggregation and metal leaching due to particle interactions, thereby greatly improving the stability and catalytic activity of the catalyst. When the mass ratio of melamine to lignin is too low, the loading amount of nickel-zinc active components will be small. By changing the mass of melamine to adjust the N doping content, the metal loading and specific surface area can be increased, the defect structure of the catalyst and the dispersion of metal clusters can be improved, and the exposure of active sites and the mass transfer process can be promoted; and appropriate nitrogen doping may help regulate the charge redistribution between the carrier and nickel, and inhibit the formation of by-products in the decomposition reaction by hindering the interaction of reaction intermediates, thereby achieving high ethanol conversion rate and high C4+ higher alcohol yield in the ethanol coupling conversion to higher alcohols using lignin-derived carbon material catalysts.

[0135] In addition, factors such as hydrothermal reaction time, hydrothermal reaction temperature and high-temperature calcination temperature also have a crucial impact on catalyst performance. The time and temperature of the hydrothermal reaction significantly affect the effects of nitrogen doping and metal loading: if the hydrothermal time is insufficient or the temperature is too low, the nitrogen doping effect will be poor, thereby reducing the metal loading and the number of acidic active sites, significantly weakening the catalytic performance. High-temperature calcination plays a key role in the morphology and stability of the catalyst. During the calcination process, the lignin-based carbon carrier gradually forms porous carbon balls and wraps the metal in them; too low calcination temperature may lead to incomplete coating, while too high calcination temperature may cause the metal active components to agglomerate, thereby affecting the catalyst performance and its structural stability.

[0136] At the same time, the choice of metal salt has a key influence on the catalytic performance of the catalyst. For example, the catalyst prepared with nickel nitrate significantly improves the ethanol conversion rate and product selectivity compared with nickel acetate. This is mainly attributed to the better solubility of nickel nitrate in water, which is conducive to forming a homogeneous solution with other reactants, promoting the uniform formation of catalyst precursors and the occurrence of homogeneous reactions during the catalytic process. At the same time, nitrate has higher thermal stability at high temperatures and is not easy to decompose, thus having less interference with catalyst preparation and catalytic reactions.

[0137] Table 1 Analysis results of Examples 1-3 and Comparative Examples 1-12

[0138]

[0139] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.

Claims

1. A method for preparing a carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin, characterized in that: The following steps are involved: (1) fully mixing a lignin solution, a nitrogen source, a nickel source, and a metal salt solution, adjusting the pH, and then performing a hydrothermal reaction to synthesize a nitrogen-doped metal-lignin precursor; (2) centrifuging and vacuum freeze-drying the doped metal-lignin precursor obtained in step (1) to obtain a metal-lignin synthetic material; (3) The metal-lignin synthetic material obtained in step (2) is calcined under a protective gas atmosphere to obtain powder particles, which are then fully ground.

2. The preparation method according to claim 1, characterized in that: The nitrogen source in step (1) is selected from one or more of melamine, cyanuric acid, disodium EDTA, N,N-dimethylformamide, hydroxylamine hydrochloride, diethylenetriamine, ethylenediamine, dicyandiamide, urea and ammonia water.

3. The preparation method according to claim 1, characterized in that: The nickel source in step (1) is selected from one or more of nickel chloride, nickel sulfate, nickel ammonium nitrate, nickel acetate, nickel oxalate and nickel nitrate.

4. The preparation method according to claim 1, characterized in that: The metal salt solution in step (1) is selected from one or more of zinc chloride solution, zinc sulfate solution, cupric chloride solution, molybdenum nitrate solution, ferric chloride solution, copper sulfate solution, manganese sulfate solution, ruthenium chloride solution, copper nitrate solution, zinc nitrate solution, zinc acetate solution, zinc oxalate solution, and zinc gluconate solution.

5. The preparation method according to claim 1, characterized in that: The molar ratio of nickel element to lignin in the nickel source in step (1) is 5-60:

1.

6. The preparation method according to claim 1, characterized in that: The molar ratio of the nickel element in the nickel source to the metal element in the metal salt solution in step (1) is 5-60:

1.

7. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (1) is 40-400° C. and the time is 1-64 h.

8. The preparation method according to claim 1, characterized in that: The calcination temperature in step (3) is 300-1000° C. and the calcination time is 2-12 hours.

9. A carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the carbon-based multi-metal catalyst for hydrothermal ammonolysis of lignin prepared according to any one of claims 1 to 8 in the preparation of higher alcohols by ethanol coupling.

Citation Information

Patent Citations

  • Preparing method for nitrogen-doped porous carbon material, catalyst comprising material and application of material

    CN104689857A

  • Lignin-based transition metal / nitrogen doped carbon material, and preparation and application thereof

    CN109012590A

  • NiSn compound nanocatalyst and preparing method and application thereof

    CN110102309A

  • Lignin nitrogen-rich carbon / zinc oxide nanocomposite as well as preparation method and application thereof

    CN112072086A

  • Bio-based carbon supported catalyst and preparation method thereof

    CN114618468A

Cited By

  • Ruthenium atom cluster composite catalyst for hydrogen production through ammonia decomposition and preparation method of ruthenium atom cluster composite catalyst

    CN120394060A

  • Preparation method of lignin carbon / alumina composite carrier nickel-molybdenum bimetallic catalyst

    CN121869380A

  • Preparation method of nickel-molybdenum bimetallic catalyst supported on lignin-carbon / alumina composite support

    CN121869380B